EFEKTIFITAS LATIHAN BEBAN DALAM MENINGKATKAN PERFORMA ATLET RENANG GAYA BEBAS: SYSTEMATIC LITERATURE REVIEW - Nurhayati Simatupang; David Gunawan Gea; Mhd Faridh Abbas Lubis; Melati Intan Siburian; Rizky Amanda Panggabean (STKIP Subang, 2026)
Freestyle swimming overall performance is pretty encouraged with the aid of muscular power, power, endurance, and biomechanical performance. Resistance education has increasingly more come to be an critical factor in swimming conditioning applications because it is believed to enhance stroke strength, start performance, turning potential, and ordinary swimming velocity. however, variations in training techniques and findings among previous studies have created uncertainty regarding the handiest resistance education approach for freestyle swimmers. therefore, this observe aimed to analyze the effectiveness of resistance education in enhancing freestyle swimming overall performance thru a systematic literature review. This take a look at used the preferred Reporting items for Systematic opinions and Meta-Analyses (PRISMA) approach. Literature changed into accumulated from databases which includes PubMed, Scopus, SPORTDiscus, and ScienceDirect the usage of key phrases associated with resistance schooling and freestyle swimming performance. The inclusion standards consisted of experimental studies and evaluate articles published between 2020 and 2026 that targeted on competitive swimmers and resistance education interventions. The findings showed that resistance schooling drastically stepped forward freestyle swimming performance, together with dash velocity, muscular strength, stroke efficiency, explosive energy, and start and flip performance. Maximal electricity training, plyometric education, and swim-unique resistance schooling were recognized as the simplest education methods. further, combining dry-land resistance training with swimming practice produced greater performance improvements as compared to swimming training on my own. In conclusion, resistance schooling is powerful in improving freestyle swimming overall performance while carried out systematically and in particular in keeping with athletes’ desires and education dreams.